2021
DOI: 10.31124/advance.13689751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MOBIS-​COVID19/29: Results as of 30/11/2020 (second wave)

Abstract: To slow down the spread of the Coronavirus, the population has been instructed to stay at home if possible. This measure consequently has a major impact on our daily mobility behaviour. But who is being affected, and how? The MOBIS-COVID-19 research project, an initiative of ETH Zurich and the University of Basel, is a continuation of the original MOBIS study. The aim of the project is to get a picture of how the crisis is affecting mobility and everyday life in Switzerland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Technology-based surveys using smartphones or dedicated GPS-devices are increasingly applied in transport studies with mainly non-representative convenience samples and are a promising avenue for future research (see, e.g., Harding 2019;Hubrich et al 2020;Molloy et al 2021). Smartphone-based surveys track respondents' trips and activities automatically with the aim to minimise respondent burden while at the same time achieving highest levels of detail and data quality.…”
Section: Evolving Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Technology-based surveys using smartphones or dedicated GPS-devices are increasingly applied in transport studies with mainly non-representative convenience samples and are a promising avenue for future research (see, e.g., Harding 2019;Hubrich et al 2020;Molloy et al 2021). Smartphone-based surveys track respondents' trips and activities automatically with the aim to minimise respondent burden while at the same time achieving highest levels of detail and data quality.…”
Section: Evolving Survey Methodsmentioning
confidence: 99%
“…Even in lockdown periods, the share of persons leaving home at least once a day hardly dropped, whereas substantial changes in travel behaviour occurred in all other dimensions such as the number of trips, mode choice, etc. (Hubrich/ Weber/Wittwer/Gerike 2020; Molloy et al 2021).…”
Section: Introduction: the Role Of Transport In Urban Researchmentioning
confidence: 99%
“…Examples of this shift are reported in Pase et al (13) and Teixeira and Lopes (14), both of whom found evidence that bicycle sharing was being used as a substitute for public transit early in the pandemic. Similarly, Molloy (15) found that the pandemic resulted in a decline in the distance traveled by transit and an increase in the distance traveled using private vehicles and active modes. Survey-based approaches complement the findings of these studies by offering insights into the factors influencing the shift in modal preferences resulting from the pandemic.…”
Section: Literature Reviewmentioning
confidence: 96%
“…It is clear that the onset of the pandemic resulted in a shift in modal preferences; however, it remains to be seen whether these shifts will remain in the post-pandemic period. Studies examining the evolution of modal preferences during the pandemic typically find that the utilization of private vehicles and active modes has rebounded more strongly than public transit (15,20). Notably, there appears to be evidence that the recovery of ride-sourcing usage is outpacing that of transit usage, which can partly be attributed to the reluctance of certain individuals to use public transit (21,22).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Sweden, COVID-19 has hit public transport hardest compared to other modes of transport and caused a significant drop in the number of passengers [23]. Based on the data from GPS in Switzerland, the average daily travel distance decreased by 60 %, while in the case of PPT, there was a decrease of more than 90 % [24]. The results of a study conducted on the changes in passenger behaviour caused by COVID-19 in several countries in South Eastern Europe show that the selection of a mode of transport depends mainly on the age and social and health status of the respondents [25].…”
Section: Introductionmentioning
confidence: 99%